Algorithm based patient care protocol to optimize patient care and inpatient stay in head and neck free flap patients. Issue 1 (December 2015) - O'Connell, Daniel; Barber, Brittany; Klein, Max; Soparlo, Jeff; Al-Marzouki, Hani; Harris, Jeffrey; Seikaly, Hadi
Abstract Objective To determine if rigid adherence (where medically appropriate) to an algorithm/checklist-based patient care pathway can reduce the duration of hospitalization and complication rates in patients undergoing head and neck reconstruction with free tissue transfer. Methods Study design was a retrospective case-control study of patients undergoing major head and neck cancer resections and reconstruction at a tertiary referral centre. The intervention was rigid adherence to a pre-existing care pathway including flow algorithms and multidisciplinary checklists incorporated into patient charting and care orders. 157 patients were enrolled prospectively and were compared to 99 patients in a historical cohort. Patient charts were reviewed and information related to the patient, procedure, and post-operative course was extracted. The two groups were compared for number of major and minor complications (using the Clavien-Dindo system) and length of stay in hospital. Results Comparing pre- and post-intervention groups, no significant difference was identified in duration of hospital stay (21.5 days vs. 20.5 days, p  = 0.750), the rate of major complications was significantly higher in the pre-intervention cohort (25.3 % vs. 14.0 %, p  = 0.031), the rate of minor complications was not significantly higher (34.3 % vs 30.8 %, p  = 0.610). Conclusion Rigid adherence to our patient care pathway, and improved charting techniques including flow algorithms and multidisciplinary checklists has improved patient care by showing a significant reduction in the rate of major complications.